2016
DOI: 10.1074/jbc.m116.753301
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax Toxin Protective Antigen Variants That Selectively Utilize either the CMG2 or TEM8 Receptors for Cellular Uptake and Tumor Targeting

Abstract: The protective antigen (PA) moiety of anthrax toxin binds to cellular receptors and mediates the translocation of the two enzymatic moieties of the toxin to the cytosol. Two PA receptors are known, with capillary morphogenesis protein 2 (CMG2) being the more important for pathogenesis and tumor endothelial marker 8 (TEM8) playing a minor role. The C-terminal PA domain 4 (PAD4) has extensive interactions with the receptors and is required for binding. Our previous study identified PAD4 variants having enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(56 reference statements)
0
10
0
1
Order By: Relevance
“…CMG2 is originally identified as a gene upregulated in endothelial cells during capillary morphogenesis [ 8 ]. It has been implicated in tumor-related angiogenesis [ 28 ] and may be a target for anti-angiogenesis therapy for cancer [ 15 , 29 , 30 ]. However, the role of CMG2 in cancer has not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…CMG2 is originally identified as a gene upregulated in endothelial cells during capillary morphogenesis [ 8 ]. It has been implicated in tumor-related angiogenesis [ 28 ] and may be a target for anti-angiogenesis therapy for cancer [ 15 , 29 , 30 ]. However, the role of CMG2 in cancer has not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PA R659S/M662R had enhanced specificity towards TEM8-expressing cells, making this PA variant another interesting tool for targeted therapies. In a recent publication, Chen et al described two further mutants of PA (PA I656Q and PA I656V) with decreased affinity towards TEM8 but with maintained high affinity for CMG2 [ 95 ].…”
Section: Retargeting Of Pamentioning
confidence: 99%
“…On the other hand, a CMG2-knockdown resulted in a decreased matrix adhesion in prostate carcinoma cells [ 15 ]. Interestingly, although the exact role of CMG2 in tumorigenesis and progression is not well described, the interest in CMG2’s angiogenic properties as targets for anti-tumor therapy are high, resulting in several reports on inhibitors putatively useful for treatment [ 44 , 45 , 46 , 47 , 48 ]. Furthermore, we demonstrated that a lower CMG2 mRNA expression was significantly associated with a worsened survival, especially in high-stage (3 + 4) soft tissue sarcomas, while there was no significant association between CMG2 mRNA expression and survival in low-stage tumors.…”
Section: Discussionmentioning
confidence: 99%